Case report of infanticide by a wild long-tailed macaque (Macaca fascicularis) - Widayati, Kanthi A.; Noerwana, Ona; Fauzi, Richsy M.; Tsuji, Yamato (Volume 151, No. 2 (April 2022) pages 751-753.)
Infanticide is common among non-human primates. There are a few cases of infanticide reported in wild groups of the genus Macaca, but in Macaca fasicularis, it is only reported under captive conditions. The present report describes the first case of infanticide observed in wild M. fascicularis in Pangandaran Nature Reserve, West Java, Indonesia, in which an adult male was seen carrying and repeatedly biting an infant. -Title page.